IDENTIFICATION AND CHARACTERIZATION OF MICROPLASTIC DEGRADING BACTERIA IN THREE LANDFILLS OF LAMPUNG PROVINCE - Hening, Jeni Latri; Kamelia, Marlina; Kesuma, Andri Jaya (BRIN - Badan Riset dan Inovasi Nasional, 2025)
Microplastics are durable and contain harmful compounds that can be absorbed into the soil and enter the food chain, posing a risk to human health and the environment. One of the efforts to reduce its impact is to utilize bacteria as biodegradation agents. The purpose of this study was to isolate and characterize microplastic degrading bacteria from three landfills in Lampung Province, and determine their degradation rate. The research method used a quantitative descriptive approach, including the isolation stage with the pouring technique, degradation tests using Polystyrene, Polyethylene Terepthalate, and Polyethylene measuring 1x1 cm and identification using Vitek-2. The results of the study from nine bacterial isolates that were successfully purified, three of them showed the highest ability to degrade. The weight reduction result on PS plastic sample was 22.2% by Bacillus circulans, PET sample was 15.9% by Pandoraea spp. and PE sample was 36.2% by Pseudomonas aeruginosa bacteria.